Teenagers' perspectives on the Canterbury earthquakes : an insight into their needs and experiences : a thesis presented in partial fulfillment of the requirements of the degree of Doctor of Clinical Psychology, Massey University, Wellington, New Zealand - Pine, Nicola Stacey (Massey University, 2015)
Natural disasters inflict physical, psychosocial, and economic impacts on individuals and their communities. Although a substantial number of disaster survivors are teenagers (13-19 years), this population group has not been widely investigated, especially regarding their views on their post-disaster needs and received supports. Such information would be important when planning post-disaster supports for current and future disaster-exposed teenagers. The aim of this research therefore, was to explore teenagers’ experiences and retrospective views of their needs, supports, and recovery following the Canterbury, New Zealand earthquakes. The first study surveyed 398 Christchurch secondary school students (aged 16-18 years [male = 169; female = 229]) who had experienced at least one of the major Canterbury earthquakes between September 2010 and June 2011. The survey’s purpose was to obtain an overview of teenagers’ experiences (including their needs and supports received), using both qualitative and quantitative data. Content analysis of this data revealed nine overall themes, including: physical basics, secondary stressors, social support, psychological impact, coping, school, support figures, gender, and recovery. Decile 2 school participants reported a need for physical basics significantly more than deciles 3, 9 and 10, and decile 10 reported a need for social support significantly more than decile 2. With gender, females reported a need for social support significantly more than males, and males reported a need for physical basics significantly more than females. Also, participants reported that their parents/caregivers understood their needs better than their siblings and friends, and their teachers were of greater help to them following the earthquakes compared to other students in their class. The second study extended the enquiry and involved six focus groups, each containing three to six students aged 16-18 years (male = 13; female = 18). Findings from the first study informed these focus group discussions, the aims of which were to gain deeper insights into disaster-exposed teenagers’ experiences, needs, and supports. The discussions were transcribed and analysed via thematic analysis. This analysis revealed seven major areas of importance, including participants’ advice for future planning and six others: individual, family, school, community, national and international. The latter six areas were incorporated into an ecological model combined with a timeline spanning from 2010 till 2013. The model demonstrated a number of notable points - for instance, immediately after the earthquakes many of the participants’ most important needs was to be in the presence of family, to know that family members were safe, and to receive comfort from them; however, three years later, participants’ concern had shifted to the rebuild of their city and their need for not only the pace to quicken, but also for youth-focused areas to be built (e.g., for recreational and leisure activities). The main recommendations from the research include: addressing acute post-disaster psychological responses early on and arranging preventative interventions; incorporating parental mental health support into youth-focused interventions; individually tailoring supports that address differences in gender, living conditions, and damage; encouraging youth to talk but not forcing them; having schools resume structured routines as soon as possible; providing psychoeducation to teachers, parents and guardians regarding typical disaster reactions and coping strategies for youth; and providing teenagers with accurate information. It is also recommended that communities provide or facilitate entertainment for youth post-disaster; that they organise youth-focused volunteer groups; involve youth in rebuild consultations; commence the rebuild of a disaster-struck city as soon as possible, and maintain gains in progress; distribute important information in multiple languages; and try to ensure that media coverage maintains a balance between both positive and negative content. Possible areas for future research include a deeper investigation into the experiences of disaster-exposed international students, the impact of the duration and permanency of relocation, and longitudinal studies into the recovery and adaptation of youth.
Keywords: Earthquakes; Psychological aspects; Disaster victims; Psychology; Adjustment (Psychology) in adolescence; Canterbury; Christchurch; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Environmental psychology